EFEK KO-KEMOTERAPI EKSTRAK BIJI PETAI (Parkia speciosa) DENGAN DOXORUBICIN TERHADAP TOKSISITAS SEL JANTUNG PADA TIKUS (Sprague dawley) MODEL KANKER LIDAH - Arya Nur Ihsan (FKG 16 UMY 057, 2016)
Doxorubicin is widely used chemotherapy agent. However, its activity induces cardiotoxicity by iron-mediated free radicals formation. Co-chemotherapy which combine conventional chemotherapy such as Doxorubicin with herbal was expected to reduce cardiotoxicity. Petai seed extract (Parkia speciosa) contains flavonoid which were allegedly suitable co-chemotherapy agent for its properties as antioxidant and iron chelating agent. The purpose of this paper was to evaluate co-chemotherapy effect of petai seed (Parkia speciosa) extract with Doxorubicin against cardiotoxicity in tongue cancer rat (Sprague dawley) model. 42 rats were collected and divided into 6 groups. Group 1 is negavtive control, group 2-6 were given exposure to carcinogenic (4-NQO) as cancer models for 12 weeks. After 12 weeks, group 2-6 recieved treatment. Group 2 were given only aquades, Group 3 were given Doxorubicin 4,6mg/KgBW and Group 4, 5, 6 were given 100, 200, 400 mg/KgBW of petai seed extract (Parkia speciosa) combined with 4,6mg/KgBW of Doxorubicin. This treatment was perfomed for 14 days. In 14th week heart tissue of rats were necropted, stained using Hematoxylin-Eosin (HE) and observed. The damage was evaluated based on its precentage and damage scale.